The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1080/0284186x.2018.1497294
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of conventional and dynamic radiotherapy planning techniques for early-stage breast cancer utilizing deep inspiration breath-hold

Abstract: Background: For breast cancer patients, radiotherapy increases the risk of cardiac disease. Conventional three-dimensional conformal radiotherapy (3D-CRT) in deep inspiration breath-hold (DIBH) has demonstrated substantial reduction in cardiac doses as compared to treatment in free breathing. The purpose of this treatment planning study is to investigate if dynamic techniques in combination with DIBH could improve the quality of the treatment plans and further reduce the doses to the heart and other organs at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
2
19
2
1
Order By: Relevance
“…In treatment plan comparison studies, often the volume receiving 95% (V95%) or 107% (V107%) of the prescribed dose is used as a criterion to evaluate the RT plan [6], while the dose received by 98% (D98%) and 2% (D2%) of the volume [7] or the dose to 99% and to maximally 2 cc [8] can also be used. Some studies use the homogeneity index (HI) and conformity index (CI) as the main target volume parameters to compare plans [8,9] or a combination of HI, V95% and V107% [10].…”
Section: Introductionmentioning
confidence: 99%
“…In treatment plan comparison studies, often the volume receiving 95% (V95%) or 107% (V107%) of the prescribed dose is used as a criterion to evaluate the RT plan [6], while the dose received by 98% (D98%) and 2% (D2%) of the volume [7] or the dose to 99% and to maximally 2 cc [8] can also be used. Some studies use the homogeneity index (HI) and conformity index (CI) as the main target volume parameters to compare plans [8,9] or a combination of HI, V95% and V107% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Aznar et al showed in a systematic review of lung doses from breast cancer RT that tangential fields spared both the ipsilateral and contralateral lung better than IMRT for whole breast RT without nodal irradiation [20]. With breathing adaption, 3D-CRT and tangential IMRT fields also had higher potential for sparing the heart compared to a partial VMAT technique [21]. These conclusions were recently validated in another study showing that the 3D-CRT in many situations is to be preferred [28].…”
Section: Discussionmentioning
confidence: 96%
“…For the ipsilateral lung, the average dose was 11.2 Gy in the period of 2010-2015 (14). For radiotherapy of patients with left-sided advanced breast cancer, 3D-CRT can cover the target with the expected dose, but fails to meet the dosimetric constraints for surrounding normal tissues (15)(16)(17)(18). Compared to 3D-CRT, IMRT and VMAT with additional multiple beam directions, can produce better conformity and homogeneity on the target, especially in the lymph node regions, and can drastically reduce the volume of the heart and lung in the radiation field (19,20).…”
Section: Introductionmentioning
confidence: 99%